1999
DOI: 10.1176/ajp.156.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline in Adulthood: An 11.5-Year Follow-Up of the Baltimore Epidemiologic Catchment Area Study

Abstract: Over a long time period, cognitive decline occurred in all age groups. Having more than 8 years of formal education was associated with less decline. However, beyond 9 years, additional education was not associated with a further reduction in cognitive decline. This suggests that a minimal amount of education during early critical periods might confer protection against cognitive decline later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
150
3
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(179 citation statements)
references
References 35 publications
16
150
3
10
Order By: Relevance
“…For example, a higher risk of Alzheimer's disease is consistently observed among those with low education levels (Evans et al 1993(Evans et al , 1997a(Evans et al , 1997bGeerlings et al 1999;Graham et al 1998;Gurland et al 1999;Hall et Prencipe et al 1996;Wiederholt et al 1993). Low education is also a predictor of cognitive decline, even in subjects < 60 years of age (Farmer et al 1995;Lyketsos et al 1999). Growing evidence indicates that various environmental influences, including traumatic injury, oxidative stress, neurotoxicants, and medications, interact with endogenous biologic factors to influence cognitive function and risk of Alzheimer's disease (Small 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a higher risk of Alzheimer's disease is consistently observed among those with low education levels (Evans et al 1993(Evans et al , 1997a(Evans et al , 1997bGeerlings et al 1999;Graham et al 1998;Gurland et al 1999;Hall et Prencipe et al 1996;Wiederholt et al 1993). Low education is also a predictor of cognitive decline, even in subjects < 60 years of age (Farmer et al 1995;Lyketsos et al 1999). Growing evidence indicates that various environmental influences, including traumatic injury, oxidative stress, neurotoxicants, and medications, interact with endogenous biologic factors to influence cognitive function and risk of Alzheimer's disease (Small 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence for a role of education in age-related cognitive decline, with several studies of normal aging reporting slower cognitive and functional decline in individuals with higher educational attainment [32][33][34][35][36][37][38][39]. These studies suggest that the same education-related factors that delay the onset of dementia also allow individuals to cope more effectively with brain changes encountered in normal aging.…”
Section: Educationmentioning
confidence: 99%
“…Epidemiological studies have shown lower prevalence or incidence of dementia in elder population with high level of education (see Meng andD"Arcy, 2012 andValenzuela et al, 2006 for a review and meta-analysis). Furthermore, neuropsychological studies have reported better cognitive test performance (Plassman et al, 1995;Wilson et al, 2009) and reduced rate of cognitive decline (Albert et al, 1995;Alvarado et al, 2002;Anstey et al, 2003;Christensen et al, 1997;Evans et al, 1993;Farmer et al, 1995;Lyketsos et al, 1999;White et al, 1994) in elders with higher levels of education. These investigations suggest that education affects the risk of late life dementia by its positive association with level of cognition or through its association with decreased rate of cognitive decline in aging.…”
Section: Introductionmentioning
confidence: 99%